2018
DOI: 10.4236/jfcmv.2018.63015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Owl-Like Airfoil Aerodynamics at Low Reynolds Numbers

Abstract: This study experimentally investigates aerodynamic characteristics and flow fields of a smooth owl-like airfoil without serrations and velvet structures. This biologically inspired airfoil design is intended to serve as the main-wing for low-Reynolds-number aircrafts such as micro air vehicles. Reynolds number dependency on aerodynamics is also evaluated at low Reynolds numbers. The results of the study show that the owl-like airfoil has high lift performance with a nonlinear lift increase due to the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As for publications considering bio-inspired morphing wings at very low Reynolds numbers [14], they usually refer to micro Unmanned Aerial Vehicles (UAVs) (see Figure 1). Anoyoji et al [15] studied owl-like airfoils for low Reynolds number flights of Micro Air Vehicles (MAVs). The NACA0012 airfoil was compared with a smooth owl-like airfoil for Re = 23,000 − 60,000.…”
Section: Introductionmentioning
confidence: 99%
“…As for publications considering bio-inspired morphing wings at very low Reynolds numbers [14], they usually refer to micro Unmanned Aerial Vehicles (UAVs) (see Figure 1). Anoyoji et al [15] studied owl-like airfoils for low Reynolds number flights of Micro Air Vehicles (MAVs). The NACA0012 airfoil was compared with a smooth owl-like airfoil for Re = 23,000 − 60,000.…”
Section: Introductionmentioning
confidence: 99%
“…Having studied the low and ultra-low Reynolds number spectrum, researchers tried to visualize the effect that the number had on the turbulence downstream of an airfoil [7,8], or the effect it had on the laminar separation bubble at the leading edge of an airfoil [9]. Others preferred to study the aerodynamics of some birds and insects, such as a dragonfly at Re below 8000 [10], or an owl [11], due to their interest in micro air vehicles with fixed wings. Having studied the behavior of aerodynamic structures (such as airfoils), there was interest in knowing what behavior the flow displays on bluff bodies at low Reynolds numbers [12].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the owl airfoil has a higher lift/drag ratio compared to NACA0002, NACA0012, and the Ishii airfoil. Anyoji et al [19] performed experiments in the wind tunnel with an owl-like airfoil, where they visualized the flow and measured the lift and drag properties. Again, the high cambered airfoil (on the pressure side) showed a better lift/drag ratio compared to NACA0012.…”
Section: Introductionmentioning
confidence: 99%